2014
DOI: 10.1073/pnas.1420601111
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory sensitization of nociceptors depends on activation of NMDA receptors in DRG satellite cells

Abstract: The present study evaluated the role of N-methyl-D-aspartate receptors (NMDARs) expressed in the dorsal root ganglia (DRG) in the inflammatory sensitization of peripheral nociceptor terminals to mechanical stimulation. Injection of NMDA into the fifth lumbar (L5)-DRG induced hyperalgesia in the rat hind paw with a profile similar to that of intraplantar injection of prostaglandin E 2 (PGE 2 ), which was significantly attenuated by injection of the NMDAR antagonist D(-)-2-amino-5-phosphonopentanoic acid (D-AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 56 publications
3
40
0
12
Order By: Relevance
“…Satellite glial cells in DRGs apparently express the NMDA-R, which might contribute to interactions with neurons (Castillo et al, 2013). NMDA-R activation in satellite cells has been linked to sensitization of nociceptors and peripheral hyperalgesia (Ferrari et al, 2014). The NMDA-R also has been identified in oligodendrocyte precursor cells, where it might function in differentiation and myelination (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Satellite glial cells in DRGs apparently express the NMDA-R, which might contribute to interactions with neurons (Castillo et al, 2013). NMDA-R activation in satellite cells has been linked to sensitization of nociceptors and peripheral hyperalgesia (Ferrari et al, 2014). The NMDA-R also has been identified in oligodendrocyte precursor cells, where it might function in differentiation and myelination (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…4). Since protein lysates from whole DRG include small and large neurons, as well as satellite glial cells, all of which express NMDARs [13; 42; 54], we used patch clamp recording to confirm neuron-specific upregulation. Patch clamp of DRG neurons confirmed that the GluN2B containing NMDARs were increased after morphine treatment, whereas AMPA, KA and mGluR1 receptor responses remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…In dorsal root ganglia (DRG) and at local sites of peripheral injury [58], for example, glutamate sensitizes sensory neurons to nociceptive stimulation in a manner dependent on NMDARs [59]. Satellite glial cells (SGCs) play an important role in this process by expressing glutamate transporters that regulate glutamate neurotransmission [60], but SGCs also express Ca 2+ -permeable, Mg 2+ -insensitive NMDARs required for sensitization of DRG neurons [61]. Although the involvement of SGC NMDARs in DRG sensitization remains to be demonstrated with conditional silencing approaches in vivo, these data highlight the possibility that PNS glial NMDARs are important nociceptive intermediates.…”
Section: Box 2 Historical Perspective On Cns Non-neuronal Nmdarsmentioning
confidence: 99%